Antecedents of perceived teacher work ability: a comprehensive model across work and non-work domains - Hlado, Petr; Juhaňák, Libor; Harvankova, Klara (Frontiers in Psychology, 2025)
IntroductionThis study investigates the antecedents of perceived teacher work ability, a critical construct for addressing challenges associated with extending working lives and maintaining sustained professional engagement in the teaching profession. Grounded in the job demands-resources (JD-R) model, this cross-sectional study investigates the relationships between job demands (quantitative, cognitive, and emotional), job resources (supervisor support, coworker support, and autonomy), burnout, and work-life conflict in shaping perceived teacher work ability.MethodsData were obtained from 841 Czech primary and lower secondary school teachers (86.1% female) with a mean age of 45.9 years (SD = 10.8). The full SEM model was developed and estimated based on the proposed hypotheses.ResultsThe findings suggest that burnout is the most significant antecedent of perceived teacher work ability, with quantitative and emotional job demands indirectly influencing it through burnout. While supervisor and coworker support directly enhance perceived teacher work ability, autonomy primarily alleviates quantitative and emotional job demands, thereby indirectly mitigating burnout. Work-life conflict partially mediates the relationship between job demands and burnout but does not directly impact perceived teacher work ability.DiscussionThese results contribute to a deeper understanding of the interplay between job demands, job resources, and burnout in enhancing teachers' capacity to meet the multifaceted demands of their profession effectively.